Development of Temperature–Time and Pressure–Time Diagrams for Diffusion Bonding Ti – AA7075 Aluminium Alloys - N. , Sithivinayagam; R. , Hariharan; R. , Praveen Rackson; V. , Pravin Kumar; Rubeshwaren (International Journal of Psychosocial Rehabilitation, 2019)
Two dissimilar aerospace materials, Cp Ti and AA7075, were joined by diffusion bonding. When joining this dissimilar material, go for the trial-and-error method. From this investigation, we developed diffusion bonding windows for Cp Ti-AA7075 of dissimilar materials. The quality of the bond of the joints was tested by microhardness, microstructure analysis, and lap shear testing.